Progesterone loaded thermosensitive hydrogel for vaginal application: Formulation and in vitro comparison with commercial product - Natalia S. Velázquez; Ludmila N. Turino; Julio A. Luna; Luciano N. Mengatto (Elsevier, 2019)
Progesterone (PGT) is a natural hormone that stimulates and regulates various important functions, such as the preparation of the female body for conception and pregnancy. Due to its low water solubility, it is administered in a micronized form and/or in vehicles with specific solvents requirements. In order to improve the drug solubility, inclusion complexes of PGT and β-cyclodextrins were obtained by the freeze-drying method. Two β-cyclodextrins (native and methylated) in two solvents (water and water:ethanol) and different molar ratio of the reagents were the variables tested for the selection of the best condition for the preparation of the complexes. The PGT/randomly methylated-β-cyclodextrin complexes were incorporated into chitosan thermosensitive hydrogels, as an alternative formulation for the vaginal administration of PGT. Neither the micro and macroscopic characteristics of the gels nor the transition time from solution to gel were modified after the complexes incorporation. In addition, chitosan gels with complexes resisted better the degradation in simulated vaginal fluid in comparison to commercial gel (Crinone®). The chitosan gel with inclusion complexes and Crinone® were tested in vitro in a diffusion assay to evaluate the delivery of the hormone and its diffusion through porcine epithelial mucosa obtained from vaginal tissue. Chitosan gel presented sustained diffusion similar to the exhibited by commercial gel. The use of chitosan gels with inclusion complexes based on cyclodextrins would be a viable alternative for vaginal administration of PGT. Keywords: Progesterone, Methylated-β-cyclodextrin, Inclusion complexes, In vitro diffusion, Drug delivery